Pengaruh Iklim Organisasi terhadap Kepuasan Kerja (Studi tentang Pengaruh Iklim Organisasi terhadap Kepuasan Kerja Pegawai Puskesmas Turen di Malang) - Anjar Wibisono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Organization climate determines the favorable or unfavorable work environment to the people inside the organization. Favorable work environment maintains the worker from turning over and affects the work satisfaction. The research objectives may be: (1) to observe the effect of leader behavior, work motivation, communication flow and decision making practice simultaneously on work satisfaction, and (2) to find out the effect of leader behavior, work motivation, communication flow and decision making practice partially on work satisfaction. Research has been classified in to explanatory research. The population includes all employees of Turen Public Health Center at Malang in 2010. Sample covers 41 respondents. Research instrument relates to questionnaire. Analysis tool considers Multiple Regression with Ftest and t-test.Results of multiple linear regression analysis indicate that the significant effect develops simultaneously and partially from all variables in the organization climate concept (variables of organization behavior, work motivation, communication flow, decision making practice) against all variables in the employee’s work satisfaction concept. It seems being confirmed through determination coefficient for organization climate effect (leader behavior, work motivation, communication flow, and decision making practice) on employee’s work satisfaction for 34.2%.Keywords: Organization Climate, Work Satisfaction